2022
DOI: 10.1002/bies.202100184
|View full text |Cite
|
Sign up to set email alerts
|

How does early‐life adversity shape telomere dynamics during adulthood? Problems and paradigms

Abstract: Although early-life adversity has been associated with negative consequences during adulthood, growing evidence shows that such adversity can also lead to subsequent stress resilience and positive fitness outcomes. Telomere dynamics are relevant in this context because of the link with developmental conditions and longevity. However, few studies have assessed whether the effects of early-life adversity on developmental telomere dynamics may relate to adult telomere dynamics. We propose that the potential links… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 121 publications
(198 reference statements)
0
21
0
Order By: Relevance
“…2). This suggests that the negative effects of growth [44], environmental stressors [46] and inbreeding [80] on early-life TL previously described in these populations may have lasting effects on TL later in life [15,78]. Recent studies have found a positive genetic correlation close to 1 between TL measurements within individuals, suggesting that the same genes are involved in controlling TL at different ages [28,38,43].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2). This suggests that the negative effects of growth [44], environmental stressors [46] and inbreeding [80] on early-life TL previously described in these populations may have lasting effects on TL later in life [15,78]. Recent studies have found a positive genetic correlation close to 1 between TL measurements within individuals, suggesting that the same genes are involved in controlling TL at different ages [28,38,43].…”
Section: Discussionmentioning
confidence: 99%
“…We found a considerable effect of hatch year, which explained 37% of the variance in ∆TL (vs. 4% in [43]). This may re ect environmental variation experienced by different cohorts in early-life such as weather conditions and competition [39,46] and suggests that there are persistent impacts of the early-life environment on TL shortening later in life [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As conceptualized above, the DC and PAR hypotheses are not mutually exclusive, as many others have noted [19, 20, 11, 21]. Adult outcomes can simultaneously be determined by the quality of the developmental environmental and how well organisms predict some feature of adulthood (Figure 1c) [18, 22].…”
Section: Introductionmentioning
confidence: 99%